BUDGET POLITICS IN DISASTER RISK REDUCTION: EVIDENCE FROM LOCAL GOVERNMENTS IN INDONESIA - Lamato, Valisa Ananta; Furqan, Andi Chairil; Paranoan, Selmita; Yudistira, Fajar Gilang (Journal of Applied Finance and Accounting, 2025)
Regions in Indonesia face high disaster risks due to the country’s geological and geographical conditions. The urgency of disaster management has become an increasingly global concern, making it essential to ensure adequate financing to support mitigation efforts and reduce future impacts and losses. This study aims to analyze the role of budgeting across various government functions in mitigating disaster risks. A quantitative approach is employed, using secondary data from provincial, regency, and city governments in Indonesia during the 2018–2022 period. The total sample includes 363 local governments with 1,815 observations. Data were obtained from the National Disaster Management Agency (NDMA), the Ministry of Finance, Statistics Indonesia (BPS), and the Ministry of Home Affairs. Data analysis was conducted using a multiple linear regression model with a random effect approach to examine the effect of budget allocation on the Disaster Risk Index (DRI). The findings show that budgets allocated to public order and safety, economic, environmental, and health functions contribute to reducing disaster risks in Indonesia. Meanwhile, budgets for general public services, culture, tourism and religion, education, social protection, as well as housing and public facilities, do not show a contribution to disaster mitigation. These findings underscore the importance of strengthening budget allocations for functions proven to be effective, as well as the need to evaluate and enhance the relevance of other functions to better support a comprehensive disaster mitigation system. Local governments also need to improve cross-sectoral integration and adopt data-driven approaches in budget planning to sustainably strengthen regional resilience.